2013
DOI: 10.1590/s0103-84782013001000010
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradação dos herbicidas imazetapir e imazapique em solo rizosférico de seis espécies vegetais

Abstract: RESUMO A fi toestimulação é uma das técnicas de fi torremediação que pode ser utilizada para a redução da concentração dos herbicidas no solo. Para tanto é necessário a seleção de plantas que estimulem a atividade dos microrganismos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Souto et al (2013) proved that plants of Stizolobium aterrimum release rhizodeposits that stimulate existing microbial activity in the rhizosphere upon degrading molecules of a formulated mixture of imazethapyr and imazapic present in soil under rice cultivation.…”
Section: Sources Of Variation Gl ------------------------------------mentioning
confidence: 99%
“…Souto et al (2013) proved that plants of Stizolobium aterrimum release rhizodeposits that stimulate existing microbial activity in the rhizosphere upon degrading molecules of a formulated mixture of imazethapyr and imazapic present in soil under rice cultivation.…”
Section: Sources Of Variation Gl ------------------------------------mentioning
confidence: 99%
“…However, it would be important to quantify the persistence of this herbicide in the soil and climate conditions of that region, considering that the half-life of herbicides in soils depends on the chemical and physical characteristics, as well as the soil microbial activity. In this sense, Souto et al (2013) found 93% imazethapyr degradation in soybean rhizosphere soil at 63 DAA. According to those authors, imazethapyr degradation is greater in soils cultivated with plant species as they provide a more favorable environment for microbial activity.…”
Section: Resultsmentioning
confidence: 85%
“…In general, researches (Artuzi & Contiero, 2006;Dan et al, 2012;Souto et al, 2013) show an absence of imazethapyr residual effects from 90 DAA. Based on these results, maize cultivation in the off-season after application Table 7 -Control of maize in desiccation under cover crops and herbicides in desiccation management.…”
Section: Resultsmentioning
confidence: 91%
“…Ryegrass can also act as a phytorremediator, decreasing the concentration of herbicide contamination in the soil (Souto et al, 2013;Galon et al, 2014). This process can occur through absorption by the plants and further metabolism or in some cases are due to stimulation of the soil microbiota associated with the remediation plants.…”
Section: Introductionmentioning
confidence: 99%